A Mini Review on Superhydrophobic and Transparent Surfaces. Issue 11 (21st September 2020) - Fei, Ling; He, Zizhou; LaCoste, Jed D; Nguyen, Thu Hoai; Sun, Yingqiang
Abstract: In recent years, self‐cleaning and transparent surfaces have been widely studied for application on smart windows, solar panels, camera lenses, and other optoelectronic devices. The self‐cleaning properties can possibly extend the lifetime of these products and decrease, even eliminate, the requirement of chemical detergents and high labor costs of cleaning. It can also promote the overall efficiency of outdoor optoelectronic devices (e. g. solar cell panels) since dirt accumulation and bacteria growth can be slowed down, even inhibited on such surfaces. In this mini review, the fundamentals and conditions that govern superhydrophobicity and transparency are introduced, followed by the discussion of roughness as the competing factor for superhydrophobicity and transparency. Representative examples of the surface design and fabrication are introduced and future perspectives are shared. This mini review can help the research community better understand such surfaces and further accelerate its development for innovative practical applications. Abstract : Superhydrophobic and transparent surfaces represent an intriguing new advancement direction in future optical/electronic industry. In this review, we have introduced fundamentals that govern superhydrophobicity and transparency and shared representative examples of surface design and fabrication. Future perspectives are also offered to inspire new research development in this area.